SISTEM INFORMASI GEOGRAFIS LOKASI SEKOLAH TINGKAT SMA SEDERAJAT PADA KABUPATEN POHUWATO - Riadi, Annahl (Teknosains: Media Informasi Sains dan Teknologi, 2016)
This study aimed to obtain accurate data on the geographic information to determine the location of high school in Pohuwato. This application uses the PHP programming language and implemented in real time. The method used in this research is descriptive research method with the stages of research that started from: the stage of the analysis, design, construction, testing, implementation, evaluation, and maintenance. System testing methods used are White Box Testing and Black Box Testing. At the White Box Testing method, based on research results and flowgraph created flowchart of the data obtained. Flowchart examined, ie the site selection process. From the results of calculations using White Box Testing method, the value of the calculation result Cyclomatic Complexity = 5, Region = 5, and Independent Path = 5 who have met the eligibility requirements in terms of software. While the results of testing using the Black Box Testing method, the value of measuring the level of ease, speed information, as well as the accuracy of the data in order to meet the eligibility requirements in the application of the system.